The Core of the Global Corporate Network - Ricardo Giglio; Thomas Lux (Networks and Spatial Economics, 2021)
We investigate the network topology of a comprehensive data set of the world-wide population of corporate entities. In particular, we have extracted information on the boards of all companies listed in Bloomberg's archive of company profiles in October, 2015, a total of almost 100,000 firms. We provide information on board membership overlaps at various levels, and, in particular, show that there exists a core of directors who accumulate a large number of seats and are highly connected among themselves both at the level of national networks and at the worldwide aggregated level.
Keywords: 000; Board and director interlocks; Network core; Network formation